Estimation of the specific enthalpy–temperature functions for plastering mortars containing hybrid mixes of phase change materials - Kheradmand, Mohammad (2014)
The use of phase change materials (PCMs) for the building sector is increasingly attracting attention from researchers and practitioners. Several research studies forwarded the possibility of incorporating microencapsulated PCM in plastering mortars for building facades, in pursuit of increased energy efficiency associated with the heat storage capacity of PCM. However, most of these studies are centred in the use of a single type of PCM, which is bound to be more adequate for a given season of the year (e.g. winter or summer) than for all the seasons. The study proposed in this work regards the evaluation of the possibility of using more than one kind of PCM, with distinct melting ranges, here termed as hybrid PCMs, in plastering mortars, to achieve adequately advantageous performance in all seasons of the year. To characterize the PCM, the specific enthalpy and phase change temperature should be adequately measured. The main purpose of this study was to show the conceptual feasibility of combining PCMs in mortars and to evaluate the behaviour of the resulting mortars with differential scanning calorimeter. The results showed that the behaviour of the mortar that contains more than one type of PCM can be predicted through the superposition of effects of the independent PCMs and no interaction occurs between them. The knowledge obtained from the experimental testing established bases for a framework of numerical simulation of real-scale applications, which can be used to ascertain the feasibility of the hybrid PCM concept for decreases in energy consumption of heating/cooling demands in the buildings.